The Effects of Quality Control System and Auditor's Competency Implementation on Auditor's Capability in Detecting Fraud on Public Accounting Office in Medan - Riva Ubar Harahap (Journal of International Conference Proceedings (JICP), 2021)
This study deals to determine the effect of Quality Control System and Auditor Competence implementation on the Auditor's Ability in Detecting Fraud partially and simultaneously in Public Accounting Firm (KAP) on Medan. This was quantitative research and used associative method. The population in this study was auditors who worked at KAP in Medan, the sampling technique used Slovin formula and the survey method, namely distributing questionnaires to research respondents was used as data collection techniques. The data analysis technique in this study used multiple linear regression analysis with the help of the SPSS version 26 program. The results were as follows: partially the implementation of the quality control system has no effect on the auditor's ability in detecting fraud, while the auditor's competence has an effect on the auditor's ability in detecting fraud. Simultaneously the implementation of the quality control system and the competence of the auditor affect the ability of the auditor in detecting fraud.